Hybrid Communication and Community Resilience: The Adaptation of the Indonesian Citizens’ Radio Community in Jepara - Essa, Essa; Fajrie, Mahfudlah; Haqqi, Muhammad Nashrul (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
The rapid development of digital technology has altered people's media consumption patterns, making traditional radio often seem less relevant. However, the sustainability of the amateur radio community demonstrates that conventional media can adapt and still play an important role. This study examines how Radio Antar Penduduk Indonesia (RAPI) Jepara maintains its relevance through a hybrid communication model that combines amateur radio with digital platforms, including WhatsApp, Telegram, and live streaming. The research focus is on how RAPI adapts to media convergence while maintaining its community-based identity. This research uses a qualitative method with an ethnographic approach. Data were collected through observation, interviews, and documentation, then thematically analyzed using the Braun & Clarke framework to uncover patterns of meaning that reflect sociocultural dynamics within the community. The analysis was enriched by Everett Rogers' theory of innovation diffusion, which explains the process of technology adoption among RAPI members. The study's results show that amateur radio remains the primary communication medium, especially in emergencies, while digital media serve to enhance efficiency, coordination, and documentation. Innovation at RAPI Jepara takes place through hands-on experience, mentoring, and trust-based interactions. This study contributes to a broader understanding of media convergence and community resilience by affirming that technological adaptation does not necessarily eliminate the collective values or social identities of communities.